Inclusão da pessoa com deficiência intelectual no mercado de trabalho: avaliação de um programa de capacitação profissional - Dota, Fernanda Piovesan [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Intellectual Disability (ID) is the deficiency that has lower rates of professional employment. Trainning programs could facilitate the insertion and maintenance of people with ID in the labor market, as well as Brazilian Law of Quotas that made mandatory to hire 2-5% of people with diabilities in companies with than 100 employees. This research aimed to assess the effectiveness of a Professional Training Program for young people with DI, both genders, aged between 14 to 18 years with diagnosis of mild DI; contrasting prospects in three groups: beginners, contractors and their employers; and comparing the evaluation pre-and a six-month post-training for beginners. Study participants were 11 beginners of the Professional Trainning Program (PTP) of an institution specialized in the care of people with diabilities; 10 people already practicing certain Labor Activity (AL) for at least two months; and 10 employees of the partner organizations of the program (ORG) that exercise direct leardership for the contracted. The PTP group was assessed by self-report scales of autonomy, self-esteem, anxiety and depression, and adaptive behavior; for AL and ORG groups, a questionnaire about professional performance and the system of the institution information were used. In the pre-training assessment, the PTP participants described themselves as pleased with the quality of their lives in general, except with their social relationships and environment; they exhibited self-esteem and high self-esteem and high self-concepts and few depressive and anxiety symptoms. On the other hand, presented low level of autonomy, and high levels of need for supports. In the post-training assessment, self-perception of the PTP was similar in regards to emotional aspects, but there was greater social participation an reduction of the need for adaptive support. Therefore, the trainning contributed to keep a positive self-perception and increase autonomy opportunities...

A deficiência intelectual (DI) é a deficiência que possui menores índices de inclusão profissional. Programas de capacitação poderiam favorecer a inserção e manutenção de pessoas com DI no mercado de trabalho, assim como a Lei de Cotas brasileira que tornou obrigatória a contratação de 2 a 5% de pessoas com deficiências nas empresas com mais de 100 funcionários. Esta pesquisa objetivou avaliar a efetividade de um Programa de Capacitação Profissional para pessoas jovens com DI, de ambos os sexos, idades entre 14 e 8 anos, com diagnóstico de DI leve constrastando as perspectivas de iniciantes, de contratados e de seus empregados e comparando a avaliação pré e seis meses pós-capacitação dos iniciantes. Participaram 11 usuários iniciantes do Programa de Capacitação Profissional (PERP) de uma instituição especializada no atendimento à pessoas com deficiência; 10 usuários exercendo há dois meses alguma Atividade Laboral (AL); e 10 funcionários das organizações parceiras do programa, que exerciam a chefia direta dos jovens contratados (ORG). O grupo PERP foi avaliado por escalas de autorrelato referentes a autonomia, autoestima, sintomas de ansiedades e depressão, e comportamento adaptativo; para os grupos AL e ORG, utilizou-s um questionário de desempenho profissional e o sistema de informações da instituição. Na avaliação pré-capacitação, o grupo PERP se mostrou satisfeito com a qualidade de suas vidas de forma geral, exceto com suas relações sociais e ambientes em que está inserido; exibiu autoestimae autoconceitos elevados e poucos sintomas depressivos e ansiosos. Por outro lado, apresentou baixo índice de autonomia, e altos índices de necessidade de apoios. Na avaliação pós-capacitação, a autopercepção do PERP foi similar para os aspectos emocionais, mas houve aumento da participação social e diminuição da necessidade de apoios adaptativos. Portanto, a capacitação contribui para a...
Inclusion of people with intelectual disabilities in the labor market: evaluation of a vocational capacity program
Keywords: Integração social; Incapacidade intelectual; Trabalho